Characterization of inextensible flows of spacelike curves with sabban frame in S₁² - Mahmut Ergüt; Essin Turhan; Talat Körpınar (Boletim da Sociedade Paranaense de Matemática, 2013)
In this paper, we study inextensible flows of spacelike curves on S₁². We research inextensible flows of spacelike curves according to Sabban frame on S₁².